2020
DOI: 10.7717/peerj.10291
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization affects maize grain yield through regulating nitrogen uptake, radiation and water use efficiency, photosynthesis and root distribution

Abstract: High external nitrogen (N) inputs can maximize maize yield but can cause a subsequent reduction in N use efficiency (NUE). Thus, it is necessary to identify the minimum effective N fertilizer input that does not affect maize grain yield (GY) and to investigate the photosynthetic and root system consequences of this optimal dose. We conducted a 4-year field experiment from 2014 to 2017 with four N application rates: 300 (N300), 225 (N225), 150 (N150), and 0 Kg ha−1 (N0) in the Northwest of China. GY was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 64 publications
(27 reference statements)
3
17
0
2
Order By: Relevance
“…Some studies also reported higher photosynthetic rates when N was applied in the form of AN than that of NN ( Song et al, 2007 ). However, some studies have suggested that higher rates of NN may inhibit the photosynthetic rates to a certain extent ( Su et al, 2020 ), while some have found lower photosynthesis when the riparian plant was grown under AN than that of NN ( Cai et al, 2021 ). In recent years, most studies have proposed that N application in the form of ammonium nitrate was more conducive to improving the photosynthetic rates and plant growth, which is consistent with the results of this experiment ( Abbas et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also reported higher photosynthetic rates when N was applied in the form of AN than that of NN ( Song et al, 2007 ). However, some studies have suggested that higher rates of NN may inhibit the photosynthetic rates to a certain extent ( Su et al, 2020 ), while some have found lower photosynthesis when the riparian plant was grown under AN than that of NN ( Cai et al, 2021 ). In recent years, most studies have proposed that N application in the form of ammonium nitrate was more conducive to improving the photosynthetic rates and plant growth, which is consistent with the results of this experiment ( Abbas et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the largest N inputs from FP (350 kg ha −1 ), there was a statistically similar yield between FP and CK. Overuse of N fertilizer has adverse effects on crops by minimizing N use efficiency (NUE) and increasing nitrate leaching losses as well as contamination of groundwater 35 , 36 . Furthermore, long-term application of ammonia-based N fertilization like urea increases soil acidity which adversely affects soil fertility where crops fail to respond with more application of N fertilizers 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Excessive nitrogen fertilizer application, on the other hand, has negative effects on crops and maize in particular, reduces nitrogen use efficiency and causes significant nitrate leaching losses because it is the primary source of nitrous oxide (N2O). As a result, nitrogen must be used in ways that meet both economic and environmental goals, which is critical for sustainable agriculture [16,17]. According to Portillo Vázquez, Pérez Soto [18], optimal fertilization is when the maximum yield: average nitrogen fertilization ratio is reached.…”
Section: Introductionmentioning
confidence: 99%